Non-exercise activity thermogenesis in the workplace: The office is on fire - Rizzato, Alex; Marcolin, Giuseppe; Paoli, Antonio (Frontiers in Public Health, 2022)
From the second half of the previous century, there has been a shift toward occupations largely composed of desk-based behaviors. This, inevitably, has led to a workload reduction and a consequent lower energy expenditure. On this point, small increments of the non-exercise activity thermogenesis (NEAT) could be the rationale to reach health benefits over a prolonged period. Different published researches suggest solutions to reverse sitting time and new alternative workstations have been thought to increase total physical activity. Therefore, the purpose of this narrative review is to summarize the current state of the research regarding the “NEAT approach” to weight-gain prevention in work environments. This review analyzes the main evidence regarding new alternative workstations such as standing, walking workstations, seated pedal, and gymnastic balls to replace a standard office chair.